Puppet Visual Adaptation on Playing Cards as Educational Media - Wiyoso, Joko (Harmonia: Journal of Arts Research and Education, 2016)
This study aims at presenting an effective media in a form of puppet picture playing cards as a means to introduce traditional puppet to the society. Research and Development (R&D) was chosen as the method to develop the playing cards. Results were presented in a form of the design of puppet picture playing cards as many as 54 cards as well as 54 puppet characters as the background pictures. The design of the playing cards is adjusted to the common playing cards which are distributed widely in the society, including both the sizes and symbols, like the pictures of spade, heart, diamond, and club. In detail, the design comprises: (1) the size of playing cards which is 6 cm width of the upper and lower sides and 9 cm length for the left and right sides. (2) The playing cardsâ background is in a bright color so does the puppet picture on the card can be seen clearly.